2011
DOI: 10.1007/s13105-011-0104-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage induced by chromium (VI) in rat erythrocytes: protective effect of selenium

Abstract: Excess chromium (Cr) exposure is associated with various pathological conditions including hematological dysfunction. The generation of oxidative stress is one of the plausible mechanisms behind Cr-induced cellular deteriorations. The efficacy of selenium (Se) to combat Cr-induced oxidative damage in the erythrocytes of adult rats was investigated in the current study. Female Wistar rats were randomly divided into four groups of six each: group I served as controls which received standard diet, group II receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 73 publications
(76 reference statements)
2
9
0
Order By: Relevance
“…Our findings revealed that short-term administration of methionine does not cause side effects on the ovary and its follicles even if used in high levels. In agreement with our results, several observations reported normal histology and correct structure and function of the ovaries in the presence of increased serum homocysteine (Soudani et al 2011;Al-Zamely et al 2001). Steegers-Theunissen et al (1992) showed a significant inverse relationship between follicular amounts of fluid homocysteine and oocyte and embryo quality in humans and suggested that the composition of follicular fluid mirrored metabolism of homocysteine in the body.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings revealed that short-term administration of methionine does not cause side effects on the ovary and its follicles even if used in high levels. In agreement with our results, several observations reported normal histology and correct structure and function of the ovaries in the presence of increased serum homocysteine (Soudani et al 2011;Al-Zamely et al 2001). Steegers-Theunissen et al (1992) showed a significant inverse relationship between follicular amounts of fluid homocysteine and oocyte and embryo quality in humans and suggested that the composition of follicular fluid mirrored metabolism of homocysteine in the body.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, compared with the control treatment, 1.31 and 4.20 mg Se/kg treatment significantly decreased PC concentration in the hepatopancreas of abalone. The result is coincident with a previous study, in which Se significantly decreased PC concentration in rat erythrocytes after Cd exposure (Soudani et al., ). All the data above suggested that Se play sn important role in protecting hepatopancreas from oxidative damage induced by Cd.…”
Section: Discussionsupporting
confidence: 93%
“…They are used in many industries as electroplating, leather tanning, and stainless-steel production (Yarkandi, 2014), but it is highly toxic causes multiorgan toxicity as hepatotoxicity, renal damage, and genotoxicity (Rana, 2008). Inside cells, Cr (VI) is reduced to Cr(III) by a variety of chemical reductants with production of reactive intermediates causing cellular damage and generation of reactive oxygen species (ROS) (Myers, 2012) that enhances oxidative stress and exert a cytotoxic effect and many diseases as renal disorders, liver disorders, inflammation and others (Soudani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%